Ultra-Wideband Noise Inhibition by Multiple Tunable PEC-PMC Sub-Cavities - Nisanci, Muhammet Hilmi; Colak, Bektas; de Paulis, Francesco (Institute of Electrical and Electronics Engineers Inc., 2025)
The reduction of electromagnetic coupling and interference is a major concern in metallic enclosures and packages. Cavity resonances act as effective coupling path transferring noise from the aggressor source to the victim device or interconnect. This paper presents an effective solution for inhibiting the noise propagation at the cavity resonances by combining the use of multiple adjacent sub-cavities characterized by tuning capability. Each sub-cavity includes an array of metal pins for realizing a Perfect Magnetic Conductor (PMC) surface whose effectiveness and corresponding cavity bandgap depends on the pin length. A moving plate is applied to each sub-cavity for regulating the pin length independently from other sub-cavities. The manufacturing tolerances require gaps between adjacent moving parts, thus allowing field leakage and possibly invalidating the ideal ultra-wideband response. A deep analysis on the impact of such gasp is carried out to demonstrate the effectiveness of the proposed solution beside although unexpected low-amplitude resonances may occur within the bandgap due to the tolerance gaps. An experimental validation is carried out covering the most representative modelled cases, further confirming the applicability and reliability of the proposed solution. © 2025 Elsevier B.V., All rights reserved.
Keywords: Bandgap; electromagnetic interfance; PEC-PMC cavity